PENGEMBANGAN SISTEM INFORMASI GEOGRAFIS PELAPORAN KERUSAKAN DAN KEGIATAN PENINGKATAN RUAS JALAN DI KOTA BANDAR LAMPUNG - Dipa Fitra Rachmanda (Jurnal Komputasi, 2021)
Roads are one of the factors that support the development of the region as a whole. Management of reporting of damaged roads at Bandar Lampung Public Works Agency still uses paper documents and the dissemination of road information to the community is not good enough. Therefore, in this study a geographic information system (GIS) will be developed as an innovation to simplify the process of reporting damaged roads to be more efficient and to better disseminate information to the public. GIS is a system designed to work with data that is spatially referenced or geographic coordinates. The design of this system uses Use Case, Activity Diagram, Sequence Diagram, and Class Diagram. The system implementation uses Google Maps API and is developed using PHP and Javascript programming languages and MySQL database. Based on the results of the analysis of system testing, the average value of the overall test obtained was 3,78. Which is looked Based on interval table of the Likert scale, the final value of test shows that GIS was successful. The results of the black box test also show that each function in each menu on the system has been running according to the procedure.